2011
DOI: 10.1210/jc.2010-1281
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Clinical Analysis of Japanese Patients with Persistent Congenital Hyperinsulinism: Predominance of Paternally Inherited Monoallelic Mutations in the KATPChannel Genes

Abstract: The majority of the Japanese patients with K(ATP) channel hyperinsulinism (84.2%) demonstrated paternally inherited monoallelic mutations that accurately predicted the presence of the focal form.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
41
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 17 publications
10
41
1
1
Order By: Relevance
“…The other interesting observation in our study was the low prevalence of monoallelic K ATP mutation (2/35; 5.7%). This is in sharp contrast to observations from genetic analysis of patients from Korea and Japan, where the single mutation rate was between 50 and 60% (Table 4) (20,23). In the study by Kapoor et al, monoallelic K ATP mutation was present in 14.6% of patients, whereas 48% of patients had monoallelic K ATP mutation in the study by Snider et al (21,22).…”
Section: Discussioncontrasting
confidence: 56%
“…The other interesting observation in our study was the low prevalence of monoallelic K ATP mutation (2/35; 5.7%). This is in sharp contrast to observations from genetic analysis of patients from Korea and Japan, where the single mutation rate was between 50 and 60% (Table 4) (20,23). In the study by Kapoor et al, monoallelic K ATP mutation was present in 14.6% of patients, whereas 48% of patients had monoallelic K ATP mutation in the study by Snider et al (21,22).…”
Section: Discussioncontrasting
confidence: 56%
“…These results are substantially higher than those of 0-8% (30,32,(36)(37)(38) of KCNJ11 mutations resulting in K ATP channel variation found in studies that analyzed all mutations of the ABCC8 and KCNJ11 genes.…”
Section: Discussionmentioning
confidence: 56%
“…Of these patients, 50% (5/10) inherited the mutation from their father. Previous studies reported that the single mutation rate was 40-43% in Western countries (37,39) and 89.5% in Japan (38) and that the paternal inheritance rate was 70 and 84.2% respectively. Our data revealed a high proportion of single mutations with a lower paternal inheritance rate.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Further clinical evaluation was not possible as the child unfortunately developed bronchopneumonia/sepsis and subsequently disseminated intravascular coagulation (DIVC) during subsequent hospitalization and died. Previous studies showed that the K ATP channel activity was seen to be decreased (Tornovsky et al, 2004;Yorifuji et al, 2011) in individuals with Gly111Arg mutant SUR1 protein. This was also demonstrated in electrophysiological studies of cultured islets which revealed defects in the electrical activity of K ATP channels (De Vroede et al, 2004).…”
Section: Discussionmentioning
confidence: 92%